TAKFIR MENURUT TAFSIR LINTAS MAZHAB - Zaimah; Sarimin Adang; Fadhila Rahmi; Abdul Rouf (STKIP Subang, 2025)
The issue of takfir has long been one of the most sensitive topics in Islamic intellectual discourse due to its theological implications and significant social consequences. Divergent interpretations of Qur’anic verses concerning faith and disbelief across Islamic madhhabs have often generated exclusive truth claims that may threaten intra-Muslim harmony. This study aims to examine the concept of takfir through cross-madhhab Qur’anic exegesis and to identify both convergences and divergences in defining the boundaries of disbelief. This research employs a qualitative library research method using a comparative-analytical approach to representative Sunni and Shi‘i tafsir works, supported by classical and contemporary literature on Islamic theology and principles of Qur’anic interpretation. The findings reveal that scholars across madhhabs generally regard takfir as a highly restricted judgment, governed by strict conditions and a strong emphasis on prudence and ethical responsibility. Differences among madhhabs primarily arise from methodological and theological frameworks rather than from a permissive stance toward declaring others unbelievers. The study concludes that a cautious, dialogical, and moderate interpretive approach is essential in addressing takfir to promote unity and strengthen religious moderation within the Muslim community.